International migration in Indonesia and its influencing factors - Salma Lova, Yuwida; Siti Aisyah (Jurnal Ekonomi, 2024)
The issue of international migration is still a concern, especially for developing countries like Indonesia, one of which is because the flow of migrants abroad can help overcome the problem of unemployment and bring large remittances to the country. This study analyzes the impact of poverty, education completion rate, open unemployment, and human development index on international migration in Indonesia from 2000 to 2021. This observation uses secondary data obtained from the Central Bureau of Statistics (BPS). The research method used in this study is multiple regression analysis using the OLS (Ordinary Least Square) method. The results showed that poverty, education completion rate, and open unemployment affect international migration, while the human development index does not affect international migration. Although a number of studies have examined the factors that influence international migration by Indonesian migrant workers, they have yielded inconsistent results. Therefore, further research should be conducted to fill this knowledge gap and provide a deeper understanding of the factors that influence international migration by Indonesian migrant workers.